Structure and optical properties of CrOxNy films with composition modulation. (2nd April 2020) - Yuan, Yanyan; Zhang, Bingye; Sun, Jian; Jonnard, Philippe; Le Guen, Karine; Tu, Yuchun; Yan, Chao; Lan, Rui
ABSTRACT: The composition and structure properties of the CrO x N y films deposited by RF reactive magnetron sputtering were investigated and correlated with their optical properties. Two kinds of targets Cr2 O3 and CrN compounds with variation of N2 and O2 gas flow were used to prepare two series of samples. The phase structure, chemical composition and optical properties of CrO x N y films were characterised by X-ray diffraction, X-ray photoelectron spectroscopy and ultraviolet–visible near -infrared spectrophotometer, respectively. The films mainly consist of Cr2 N and CrO3 phases. The Cr/ON ratio derived by XPS varies with the variation of nitrogen with Cr2 O3 target. But only lower nitrogen content is detected with variation of oxygen using CrN target. The CrO x N y films with higher nitrogen content possess high absorbance around at 35% in the visible light range no matter the target.